The Problem of State Bankruptcy - Kasperowicz-Stępień, Alicja (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Financial problems in many European countries have increasingly brought the issue of state bankruptcy to the fore. The rapid increase in a country’s debt to GDP ratio can cause difficulties in the use of debt and thus reduce the country’s creditworthiness. This paper presents the problem of state bankruptcy and debt restructuring methods used in the global economy.